Comparison between somaclonal variation in intact plants and mericlones of tomato cv. Mt1 and between antioxidative properties of mature and young tomato fruits - Mahadi, Siti Nuratiqah (2015)
Tomato Lycopersicon esculentum is a member of the Solanaceae family. Most of the studies on micropropagation of tomato use stem, hypocotyl, leaf disc and cotyledon as the explant instead of young shoot apical meristem (SAM). Therefore, the first objective of this study was to evaluate the effect of Indole Acetic Acid (IAA) and Kinetin (KIN) on plantlet regeneration from SAM. SAM was isolated from 6-days-old germinating tomato seedling and was then cultured into liquid Murashige and Skoog (MS) medium supplemented with different concentrations of IAA and KIN, respectively, and a combination of both hormones in the ranges of 0.1-0.2 mg/l while liqiud MS medium alone served as control. Results showed that SAM was able to regenerate to an entire plant in all treatments. The highest significant mean in percentage of explant survival shown in treatment 8 (T8) which is liquid MS medium supplemented with combination of 0.05 mg/L IAA + 0.1 mg/L KIN with 66%. T8 was also the best treatment in the in vitro regeneration of SAM with an average plant height (4.6 cm), number of leaves (9) and number of roots (7). The second objective was to study the variation on morphology, anatomy and primary metabolites content between tomato intact plant and mericlones. Our findings indicated that the morphology, histology and contents of primary metabolites of all mericlones were almost similar with intact plants; t-test (p>0.05). Both intact plant and mericlone has similar odd pinnate leaf, acute leaf tip, oblique leaf base, serrate leaf margin and reticulate vein. Intact plant has higher total chlorophyll and total soluble protein content but lower in total carbohydrate content compared to mericlones. However, no significant difference observed (p>0.05) excluding total chlorophyll content. Therefore, it was concluded that SAM serves as a suitable explant that can regenerate true mericlones and combination hormone of 0.05 mg/L IAA + 0.1 mg/L KIN gave the best response in the growth development of the mericlones. The third objective of this study was to compare the antioxidant properties and antioxidant activity between mature and young fruits of tomato plant cv. MT1 that was grown in conventional propagation. Total carotenoid, flavonoid and phenolic content of mature and young tomato fruit were measured. 2,2- diphenyl-1-picrylhidrazyl (DPPH) radical scavenging activity and reducing power analysis were employed to measure antioxidant activity of both mature and young fruits. Fruit sample (200 mg) was extracted and diluted into a series of concentration (0.5, 1, 2, 5, and 10 mg/ml). Mature fruit was found to have significantly (p<0.05) higher total carotenoid, total flavonoid and total phenolic content, and higher antioxidant activity. In addition, mature fruit has lower IC50 value when compared to young fruit with 6.00 ± 0.03 and 8.86 ± 0.03 µg/ml respectively. Hence, it was concluded that mature tomato fruit of tomato plant cv. MT1 showed higher contents of antioxidant properties and higher antioxidant activity in comparison to the young tomato fruit of tomato plant cv. MT1.